The Influence of Apparatus Competence, Internal Control and Financial Systems on Fraud Prevention with Morality as Moderation - Andrini Akbar; Iskandar Muda; Amlys Syahputra Silalahi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this study is to determine the effect of apparatus competence, internal control and financial systems on fraud prevention in the management of village fund financial reports in Rokan Hulu Regency. In addition, this study also tests individual morality as a moderating variable for the relationship between internal control and financial systems on fraud prevention in the management of village fund financial reports in Rokan Hulu Regency. This research design uses a quantitative approach with the type of primary data that is the sample of village officials from 139 villages in Rokan Hulu Regency. The sample determination was done using the Cluster random sampling technique. The minimum sample in this study was 246. The data analysis technique used in this study uses SEM (Structural Equation Modeling) with the help of IBM-Amos software. The results of this study indicate that internal control and financial systems have an effect on fraud prevention, but the competence of the apparatus does not have an effect on fraud prevention. In addition, individual morality is not able to moderate the effect of the competence of the apparatus and financial systems on fraud prevention. However, it is able to moderate the effect of internal control on fraud prevention.